Parental care does not compensate for the effects of bad years on reproductive success of a vagile bird. (25th April 2021) - Stojanovic, D.; McEvoy, J.; Alves, F.; Rayner, L.; Heinsohn, R.; Saunders, D.; Webb, M.
Abstract: Life history theory predicts that long‐lived animals trade off the costs of reproduction against individual survival. If the costs of reproduction are too high, animals should prioritize their own survival. During bad times, mobile animals may be able to compensate for local food shortages by travelling further to provision their offspring. But, whether inherent mobility alleviates individual fitness costs of this parental strategy is not known. We studied parental investment and breeding success of long‐lived, nomadic, migratory swift parrots Lathamus discolor over two successive years at the same site where food abundance went from locally low to high. We hypothesize that in a bad year, swift parrots should adjust their parental strategy by foregoing breeding altogether, producing smaller clutches/broods or reducing provisioning investment. Fewer swift parrots bred locally when food was scarce. In the bad year, clutch and brood sizes were smaller and nestlings were >20 g lighter (approximately 28% of mean body mass) than in the good year. Compared with the good year, fathers spent longer foraging, less time at the nest and travelled further during provisioning trips in the bad year. Although limited to only 2 years, our results suggest that mobile species may attempt to mitigate the effects of a bad year on their reproductive success by rearing fewer offspring and investing more in provisioning behaviour, but this strategy may not necessarily compensate for environmental conditions. Abstract : We studied parental investment and breeding success of long‐lived, nomadic, migratory swift parrots Lathamus discolor over two successive years at the same site where food abundance went from locally low to high. In the bad year, fewer swift parrots bred, clutch and brood sizes were smaller, nestlings were underweight, and fathers worked harder to provision their broods. Our results suggest that mobile species may attempt to mitigate the effects of a bad year on their reproductive success, but their strategy may not necessarily compensate for environmental conditions.